Transformative learning of mentors from an immigrant workplace connections program. Issue 1 (2nd January 2017) - Shan, Hongxia; Butterwick, Shauna
ABSTRACT: Mentorship programs have been deployed within immigrant and settlements services to integrate newcomers to the Canadian labor market. These programs are often assessed for their impacts on immigrant mentees. Little attention has been paid to how they may have influenced mentors. In this context, this study, from the perspective of transformative learning, examines the experiences of 19 mentors who were involved in a mentorship program designed to enhance the employment prospects for immigrant professionals in Canada. Findings indicated that in the process of mentoring immigrants with diverse backgrounds, mentors engaged in both informational and transformational learning. Through informational learning, the mentors expanded their cultural and work-related knowledge, hence their life horizons. For some mentors, their learning was also transformational. Some developed new awareness of and relation to the self. Some also started recognizing the structural and cultural barriers facing newcomers, and sometimes taking actions to effect social change. Both kinds of learning – informational and transformational – we argue, may contribute to disrupting relations of inequality between newcomers and the host society. The study suggests ways through which mentoring programs can contribute to a two-way process of integration involving changes and learning for both newcomers and the host society.